MACROALGAE DIVERSITY AND LIFE FORMS OF INTER-TIDAL ROCKY SHORES - Zakaria, Muta Harah; Chia, Wong Siaw; Bujang, Japar Sidik; Arshad, Aziz; Ogawa, Hisao (Marine Research in Indonesia, 2007)
A study on macroalgae diversity and life form was carried out at inter-tidal rocky shores of Similajau National Park, Bintulu, Sarawak. Thirty five species were identified in this study, of which 15 belong to the division Rhodophyta, 12 to the Chlorophyta and 8 to Phaeophyta. Fifteen species are new records to the Park. Irrespective of areas, macroalgae from the three divisions; Chlorophyta, Phaeophyta and Rhodophyta did not show any distinct zonation. There was high number of macroalgae species in rocky area related to the sandy area. The high representation of macroalgae from rocky area reflects the availability of stable substrate and microhabitats for the occurrence and diversity of macroalgae species. The sandy area lacks hard structure responsible for the relatively low diversity of macroalgae. Four types of macroalgae life forms were identified namely epilithic, epipelic, epizoic and epiphytic. The general distribution, occurrence and a list of the macroalgae is presented.